Ouran High School Host Club. Vol. 07 - Hatori, Bisco (Shojo beat manga., 2006)
Hunny's little brother, Chika, pays a visit to the Host Club--and immediately starts attacking Hunny, using all his martial-arts prowess against his older brother! Chika seems to be the absolute opposite of his sweets-loving, Bun-Bun-toting sibling, but why is he so angry with Hunny? The Host Club is determined to find out the cause.